ORIGIN OF CONDITIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The origin of the Turkic-speaking Uzbek ethnic stratum referred to as Sart dates back to the early Middle Ages, i.e. during the Arab invasion, two more categories of Arabs entered Central Asia along with the conquering Arab army. While the first of these were the descendants of the Prophet (these were mainly engaged in the propaganda of Islam among the population), the second were Arab traders who came in under the name of Tazik. Sart was a Turkic language, or language, spoken by the inhabitants of Central Asia. Although the issue of ethnic identity in pre-Soviet Central Asia is highly controversial, there is a general perception that the Turks are the ones who grazed in various settlements scattered throughout the region.